IBM PowerAI : deep learning unleashed on IBM Power Systems Servers - Quintero, Dino (IBM redbooks., 2018)
While targeting technical readers, this IBM Redbooks publication is for anyone looking to understand the IBM PowerAI Deep Learning architecture, framework configuration, application and workload configuration, and user infrastructure. --